Understanding Experiences of Chronic Illness from the Patient Perspective - Cinthia De La Rosa; Rainer Soriano; Valerie Parkas; Neloofar Naderi (Association of American Medical Colleges, 2014)
Abstract This resource documents the longitudinal clinical experience (LCE) introduced at the Icahn School of Medicine. This longitudinal program allows the students to further understand the experience of illness from the patients' perspective, learn from the clinician's approach in caring for patients with chronic illnesses, and identify methods to navigate the healthcare system in caring for chronically ill patients. The LCE program partners a patient cared for by an Icahn School of Medicine faculty member with two first-year medical students. The students establish a long-term relationship with the patient and the physician over the length of the course. Students observe first-hand challenges faced by patients living with chronic illnesses, how their chronic medical conditions impact their quality of life, and the coping mechanisms they have developed to live with the challenges their chronic illnesses pose. During their time with the patient, students reflect on the patient's experience through a series of written assignments related to the patient's life history, medication management and reconciliation, and their own reflection. They also can select from a list of additional reflection assignments as they relate to the patient. Topics for these additional reflections include: behavior modification, health insurance, health literacy, advance care planning, home environment assessment, nutrition assessment, and social determinants of health. When asked to reflect on this experience, some students disclosed a nonexistent, minimal, or unclear relationship mainly due to limited contact with care team and unfamiliarity of patients' needs. However, many students had positive encounters and established meaningful relationships with their LCE patient and felt their patient was trustworthy, respectful and welcoming.